Use of Off-Label Targeted Therapies in Refractory Sarcomas: Analysis of Pediatric Data from the French Registry Observatoire de l'Utilisation des Thérapies Ciblées dans les Sarcomes - Garnier, Nathalie; Bertrand, A.; Libbrecht, C.; Corradini, N.; Pacquement, H.; Gentet, J. C.; Lervat, C.; Girodet, M.; Bouclier, L.; Ray-Coquard, I.; Marec-Berard, P. (Journal of Pediatric Biochemistry, 2016)
Targeted therapies (TT) are used in pediatric patients based on the data from adult literature. In 2008, the French Sarcoma Study Group and the Bone Tumor Group (Groupe Sarcome Français-Groupe d'étude des Tumeurs Osseuses) opened Observatoire de l'Utilisation des Thérapies Ciblées dans les Sarcomes (OUTC'S), a national registry of targeted off-label sarcomas therapies. All patients registered in the OUTC'S database and treated in pediatric oncology units were included in this analysis. We describe TTs using off-label and off clinical trial practices for children with sarcoma. We analyzed TT tolerability and efficacy for 34 patients with osteosarcoma (n = 20), Ewing sarcoma (n = 9), clear cell sarcoma (n = 1), synovialsarcoma (n = 1), epithelioid sarcoma (n = 1), myofibroblastic tumor (n = 1), and desmoid tumor (n = 1) who were registered from six pediatric centers. In total, 38 different TT courses were administered. The median age was 15 years (5–23) and 18.5 years (7–27) at diagnosis and at the time of starting TT, respectively. The decision to initiate TT was taken in a multidisciplinary board in 92% of the cases. TT included sirolimus (alone or in association with other treatments), sunitinib, sorafenib, cetuximab, imatinib, and crizotinib. The median duration of treatment was 109 days (21–515). Of the 34 patients, 6 had a partial response with a median response duration of 3.72 months (2.08–30.8) and 10 had a stabilization of the disease with a median duration of 3.63 months (0.75- 16.89). In our cohort, overall survival and progression-free survival were 8.68 months (95% confidence interval [CI]: 5.85–11.50) and 3.29 months (95% CI: 2.69–3.88), respectively. Grades 3 and 4 toxicities were reported for seven patients (26%) and were most commonly hematological. Patients under 15 years of age did not show severe toxicity. Hence, TT is an acceptable therapeutic option for refractory pediatric sarcomas. It is very important to continue collecting data and develop phase I/II protocols.
Keywords: targeted therapies; sarcomas; pediatric